Studi filariasis berbasis pemeriksaan laboratorium di Kota Semarang - Ririh Jatmi Wikandari; Dina Afrianti; Surati Surati (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Filariasis is a disease caused by parasitic nematodes of Filariae. Filariasis is caused by filarial worm species, namely Wuchereria bancrofti, Brugia malayi, and Brugia timori. This disease is transmitted through the bite of infected mosquitoes (Anopheles, Aedes, and Culex). Symptoms of filariasis in men or women include damage to the lymphatic system swelling of the arms, legs, and genitals, which causes pain, decreased productivity, and social problems. Filarial diagnosis through examination of blood smears to detect filarial parasites in the blood, accompanied by hematological and clinical chemical examinationsObjective: This study aimed to describe filariasis through blood tests (blood smears, hematological examinations, and clinical chemistry examinations) on filariasis respondents using a cross-sectional approach.Method: This type of descriptive research uses a cross-sectional approach. The research subjects were 6 filarial respondents in Pedurungan District, Semarang City. The examination was conducted at the Tologosari Wetan and Kulon Health Centers on September 12-18, 2020. Secondary data collection was obtained from capillary blood examination using thin blood smears, automatic hematological examination using a hematology analyzer, and clinical chemistry examination using the spectrophotometer method with a spectrophotometer. The research data was processed and analyzed using Univariate analysis using maximum, minimum, and average values.Results: Hematological examination for hemoglobin level of 12,5 g%, leukocytes 3200 cells/ml, platelets 137.00 cells, erythrocytes 4,07x106 cells, lymphocytes 35 cells, neutrophils 73 cells, eosinophils 1 cell, monocytes 9 cells, MCH 30,78 pg, MCV 86,48 fl, MCHC 36,24 g/l and clinical chemistry examination results for cholesterol 145,7 g/dl and triglycerides 104,6 g/dl. Meanwhile, on examination of thin blood smears, microfilariae were found.Conclusion: The results of the blood smear evaluation showed an abnormality in the size of the red blood cells in the form of microcytic (smaller red blood cell size), and filarial findings were found. In contrast, hematology and clinical chemistry examination results obtained normal results.